The Beauty of Humanity Movement - Gibb, Camilla (New York : Penguin Press, 2011)
Searching for answers about her dissident father's disappearance, a Vietnamese-American art curator returns to her ancestral country, where she meets a venerable pho stall soup maker and a dynamic young tour guide whose historical and cultural insights irrevocably shape her life.
Originally published: Toronto : Doubleday Canada, 2010.
edited hb 2015-06-16
Keywords: Dissenters -- Vietnam -- Fiction; Vietnamese Americans -- Fiction; Dissent -- Vietnam -- Fiction; Vietnamese Americans -- Fiction; Vietnam -- Fiction; Vietnam -- Fiction